1993
DOI: 10.2307/1242961
|View full text |Cite
|
Sign up to set email alerts
|

Live Cattle Futures Response to Cattle on Feed Reports

Abstract: Knight‐Ridder surveys provide prerelease expectations of the information in the Cattle on Feed reports. The Knight‐Ridder information is employed here, in accordance with the efficient markets hypothesis, to identify the unanticipated information provided in Cattle on Feed reports. Rational expectations theory is used to test Knight‐Ridder forecasts for unbiasedness, efficiency, and forecast performance. The forecasts mostly satisfy rationality conditions. Live cattle futures prices respond to unanticipated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…The news component of these reports, or “market surprise,” (Stmfalse) is typically computed as the difference between the actual announcement ( A t ) and the market's expectation of the announcement before the release: Stm=AtEtτ[]At. Because it is impossible to obtain the true belief of numerous market participants, the average or the median of industry analysts' estimates have been generally used as a proxy for E t − τ [ A t ] (e.g., Colling and Irwin ; Grunewald, McNulty, and Biere ; Garcia et al ; Egelkraut et al ). We follow the same approach to construct private expectations in this study.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The news component of these reports, or “market surprise,” (Stmfalse) is typically computed as the difference between the actual announcement ( A t ) and the market's expectation of the announcement before the release: Stm=AtEtτ[]At. Because it is impossible to obtain the true belief of numerous market participants, the average or the median of industry analysts' estimates have been generally used as a proxy for E t − τ [ A t ] (e.g., Colling and Irwin ; Grunewald, McNulty, and Biere ; Garcia et al ; Egelkraut et al ). We follow the same approach to construct private expectations in this study.…”
Section: Datamentioning
confidence: 99%
“…Because it is impossible to obtain the true belief of numerous market participants, the average or the median of industry analysts' estimates have been generally used as a proxy for E t − τ [A t ] (e.g., Colling and Irwin 1990;Grunewald, McNulty, and Biere 1993;Garcia et al 1997;Egelkraut et al 2003). We follow the same approach to construct private expectations in this study.…”
Section: Datamentioning
confidence: 99%
“…Papers by Gorham (1978), Ho¡man (1980), Miller (1979, Sumner and Mueller (1989), Colling and Irwin (1990), and Grunewald, McNulty and Biere (1993), have demonstrated that futures prices react quickly to the release of USDA livestock and crop reports. Sumner and Mueller (1989) investigated the informational content of USDA corn and soybean harvest forecasts.…”
Section: Event Studies and E¤ciency Implicationsmentioning
confidence: 99%
“…However, with options available, traders have a means of hedging existing futures positions and are not forced to liquidate. Thus, prices do not show significant adjustments.2 An alternative group of studies investigates price responsiveness to unanticipated and anticipated information [Miller ( 1979); Colling and Irwin (1990); Garcia and Leuthold (1992); Runkle (1992); Grunewald et al (1993)l. Most of these studies use an average of forecasts 'The studies by Fackler and Sumner and Mueller consider the impact on the new-crop contract futures price, whereas Milonas considers the impact on the cash price.…”
Section: Usda Information Impacts On Commodity Futures Pricesmentioning
confidence: 99%